2016
DOI: 10.1002/ange.201510504
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Magnesium‐Substituted Polystibides [(LMg)4Sb8]

Abstract: Redoxr eactions of [(L 1,2 Mg) 2 ]a nd Sb 2 R 4 (R = Me, Et) yielded the first Mg-substituted realgar-type Sb 8 polystibides [(L 1,2 Mg) 4 (m 4 ,h 2:2:2:2 -Sb 8 )] (L 1 = HC[C(Me)N(2,4,6-Me 3 C 6 H 2 )] 2 ,L 2 = HC[C(Me)N(2,6-i-Pr 2 C 6 H 3 )] 2 ). Compounds [(L 1,2 Mg) 2 ]s erve both as reducing agents,i nitiating the cleavage of the Sb À Cbonds,and as stabilizers for the resulting Sb 8 polyanion. The polystibides were characterized by NMR and IR spectroscopies,elemental analysis,and X-ray structure analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…In 2016, Schulz et al. reported on the synthesis of Mg‐substituted realgar‐type polystibides [(L 1, 2 Mg) 4 ( μ 4 , η 2:2:2:2 ‐Sb 8 )] (L 1 =HC[C(Me)N(2,4,6‐Me 3 C 6 H 2 )] 2 , L 2 =HC[C(Me)N(2,6‐i‐Pr 2 C 6 H 3 )] 2 ), which arose from the cleavage of Sb 2 R 4 (R=Me, Et) using Mg I reductants . It has not been reported that similar compounds are accessible using elemental Sb itself.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2016, Schulz et al. reported on the synthesis of Mg‐substituted realgar‐type polystibides [(L 1, 2 Mg) 4 ( μ 4 , η 2:2:2:2 ‐Sb 8 )] (L 1 =HC[C(Me)N(2,4,6‐Me 3 C 6 H 2 )] 2 , L 2 =HC[C(Me)N(2,6‐i‐Pr 2 C 6 H 3 )] 2 ), which arose from the cleavage of Sb 2 R 4 (R=Me, Et) using Mg I reductants . It has not been reported that similar compounds are accessible using elemental Sb itself.…”
Section: Methodsmentioning
confidence: 99%
“…[12] It has not been reported that similar compounds are accessible using elemental Sb itself.T hus,w ef elt challenged to investigate whether f-element polystibides could be obtained from such areadily available source. [12] It has not been reported that similar compounds are accessible using elemental Sb itself.T hus,w ef elt challenged to investigate whether f-element polystibides could be obtained from such areadily available source.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10e,f] We recently showed that the reaction of Sb(NMe2)3 with L 2 Ga yielded the distibene L 2 Ga(Me2N)Sb=SbGa(Me2N)L 2 , which upon heating gave [{L 2 (Me2N)Ga}2Sb4], the first Sb analogue of bicyclo[1,1,0]butane formally containing a [Sb4] 2dianion. [11] In addition, the reaction of distibines R4Sb2 (R = Me, Et) containing divalent Sb atoms with [L 2,3 Mg]2 yielded the Zintl-type ions [(L 2,3 Mg)4(4, 2:2:2:2 -Sb8)] {L 3 = HC[C(Me)N(2,4,6-Me3C6H2)]2}, [12] while the analogous reaction with L 2 M (M = Al, Ga) proceeded with insertion of L 2 M into the Sb-Sb bond and subsequent formation of L 2 M(SbEt2)2. [13] We now focused on reduction reactions of cyclo-tetrastibine [Cp*Sb]4, which formally contains monovalent Sb atoms, and report herein on the synthesis of…”
Section: Introductionmentioning
confidence: 99%